Steady Q-switched erbium-doped fiber laser pulse generation by exploiting spider silk as a passive saturable absorber - Muhammad, Nur Ainnaa Mardhiah; Awang, Noor Azura; Basri, Hatijah; Abd Latif, Amirah; Zalkepali, Noor Ummi Hazirah Hani; Nik Mahmud, Nik Noor Haryatul Eleena (Elsevier, 2024)
Spider silk is a biomaterial composed of natural protein that possesses unique strength and biocompatibility. Spider silk was explored for the first time that act as a potential saturable absorber (SA) for steady Q-switched erbium-doped fiber laser pulse generation around 1569 nm. The biocompatibility of spider silk SA will lead to the realization of an environment that is free from hazardous precursors and undesirable byproducts. In this study, spider silk was directly deposited onto the end face of the fiber ferrule to complete the fiberized SA assembly. In optical characteristic context, the modulation depth of spider silk SA used was 26 % and its saturation intensity was 0.02 MW/cm2 . Results showed that self-started Q-switched at 30 mW threshold pump power was achieved. It was also interesting to find that the repetition rate of spider silk SA increased from 7 kHz to 29 kHz while the pulse width decreased from 32 µs to 10 µs. The signal-to-noise ratio (SNR) of the fundamental frequency was 54 dB, confirming the good stability of the pulsed laser. The highest output power and pulse energy measured at the pump power of 200 mW were 0.04 mW and 1.4 nJ respectively. In a nutshell, these results indicate that spider silk can be a viable alternative to real SA for producing laser at the 1570 nm region and spider silk-based SA can be equally with or even superior to the commonly employed SAs, which then opens up new possibilities for pulsed laser source applications.